Immunofibroblasts are pivotal drivers of tertiary lymphoid structure formation and local pathology - Nayar, S; Campos, J; Smith, CG; Iannizzotto, V; Gardner, DH; Mourcin, F; Roulois, D; Turner, J; Sylvestre, M; Asam, S; Glaysher, B; Bowman, SJ; et al. (National Academy of Sciences, 2019)
Resident fibroblasts at sites of infection, chronic inflammation, or cancer undergo phenotypic and functional changes to support leukocyte migration and, in some cases, aggregation into tertiary lymphoid structures (TLS). The molecular programming that shapes these changes and the functional requirements of this population in TLS development are unclear. Here, we demonstrate that external triggers at mucosal sites are able to induce the progressive differentiation of a population of podoplanin (pdpn)-positive stromal cells into a network of immunofibroblasts that are able to support the earliest phases of TLS establishment. This program of events, that precedes lymphocyte infiltration in the tissue, is mediated by paracrine and autocrine signals mainly regulated by IL13. This initial fibroblast network is expanded and stabilized, once lymphocytes are recruited, by the local production of the cytokines IL22 and lymphotoxin. Interfering with this regulated program of events or depleting the immunofibroblasts in vivo results in abrogation of local pathology, demonstrating the functional role of immunofibroblasts in supporting TLS maintenance in the tissue and suggesting novel therapeutic targets in TLS-associated diseases.